The Effects of Tactical Game Approach Learning Management Combined with Skill Twins 2 Game on Learning Basic Football Dribbling Tactics for 5th Grade Students - หล่อเจริญ โชติพัฒน์; สุขพันธ์ ศุภรักษ์; รัตนหิรัญ ธิติวุฒิ; จุ่นเกตุ ไพรัช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: 1) compare the learning achievement in Basic Football Dribbling Tactics before and after instruction using the Tactical Game Approach learning method with the Skill Twins 2 game for Grade 5 students and 2) examine the satisfaction of Grade 5 students with the Tactical Game Approach learning method with the Skill Twins 2 game. The sample group consisted of 33 Grade 5/2 students from St. Andrews School using cluster random sampling method. The research instruments included the learning management plan, the learning achievement test, and the satisfaction questionnaire. The data included analyzed using the mean, standard deviation, and the Dependent Sample t-test. The research findings indicated that 1) Students who learned Basic Football Dribbling Tactics using the learning management method of Tactical Game Approach combined with the Skill Twins 2 game, the average score after learning (Mean = 11.27, S.D.= 1.46) showed a significant increase in their average score than before learning (Mean = 8.09, S.D.= 1.59) at the statistical significance level of .05, and 2) The students expressed overall satisfaction with the Tactical Game Approach learning method combined with the Skill Twins 2 game at a high level (Mean = 4.47, S.D.= 0.34).